(NoSNOWY MNOGOPOLQRNOSTI (B/s - (NlENSKIJ(B, (NwASILIJ wASILXEWI^s; (NkO^NEW(B, (NaLEKSANDR gEORGIEWI^s ((NiRKUTSK (B:s (NiZD(B-(NWO iRKUT(B. (NGOS(B. (NUN(B-(NTA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 184-185 (24 (NNAZW(B.)s
Keywords: (NmATEMATIKA (B- (NmETODOLOGIQs; (NfIZIKA (B- (NmETODOLOGIQs; (NmNOGOZNA^NOE SOOTWETSTWIEs